(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Researchers in economics, engineering, environmental science, sociology, medical science and numerous different fields manage the complexities of modeling questionable data. Traditional methods are not constantly fruitful, in light of the fact that the vulnerabilities appearances in these spaces might be of different sorts. The majority of the current mathematical tools for formal modeling, reasoning and processing are Crisp, deterministic and exact in character. However, all things considered, circumstance, the issues in Economics, Engineering, condition, Social science, Medical science and so forth, don’t generally include crisp data. Therefore, we can’t effectively by utilizing the traditional old style methods as a result of different sorts of vulnerabilities in this issue. In this Article, we studied the previous reviews of Literature on structures of fuzzy soft isomorphism and q-fuzzy soft normal subgroups.